2002
DOI: 10.1524/ract.2002.90.9-11_2002.705
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of quantitative X-ray diffraction measurements of geologic materials to cesium sorption

Abstract: Quantitative XRD / Rietveld analysis / Cesium / Sorption / Illite / SmectiteSummary. The amounts of clay minerals in geologic samples from the Australian arid zone were measured using the SIROQUANT program, which quantifies mineral abundances from X-ray diffraction patterns using the Rietveld method. The sorption of trace cesium on the same samples was investigated in batch experiments. The statistical relationships between the Cs distribution coefficients (K d values) and the smectite, illite and kaolinite co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…The accuracy of the K d values from the diffusion tests is adversely affected by the strong sorption of 137 Cs, which limited its travel through the clay. Nevertheless the K d values are similar to those from the batch tests on sub-specimens, however, this may reflect specimen variability as Payne et al (2002) reported values for the clay from 4300 L kg À1 to 5060 L kg À1 and for the quartzite between 1040 L kg À1 and 6970 L kg À1 . These values are sensitive to clay, and particularly illite content.…”
Section: Diffusion Test Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The accuracy of the K d values from the diffusion tests is adversely affected by the strong sorption of 137 Cs, which limited its travel through the clay. Nevertheless the K d values are similar to those from the batch tests on sub-specimens, however, this may reflect specimen variability as Payne et al (2002) reported values for the clay from 4300 L kg À1 to 5060 L kg À1 and for the quartzite between 1040 L kg À1 and 6970 L kg À1 . These values are sensitive to clay, and particularly illite content.…”
Section: Diffusion Test Resultssupporting
confidence: 70%
“…The batch K d values (Payne et al, 2002(Payne et al, , 2009 were also measured under a saturated CaSO 4 solution, similar to that in the diffusion tests. The K d value estimated for 137 Cs from the diffusion tests was 5000 L kg À1 for both soils.…”
Section: Diffusion Test Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…One recent example is the use of isotopes at trace levels to identify preferential sorbing materials in mixed environmental sorbents (Payne et al, 2002). This application is significant because highly specific surface sites probably play dominant roles in environmental reactions of trace metals.…”
Section: Mechanistic Interpretationsmentioning
confidence: 99%